2021
DOI: 10.1051/0004-6361/202039614
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned disks induced by infall

Abstract: Arc- and tail-like structures associated with disks around Herbig stars can be a consequence of infall events occurring after the initial collapse phase of a forming star, consistent with the observation of luminosity bursts. An encounter event of gas with an existing star can lead to the formation of a second-generation disk significantly after the initial protostellar collapse phase. Additionally, observations of shadows in disks can be well described by a configuration of a misaligned inner and outer disk, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 105 publications
(123 reference statements)
5
25
0
Order By: Relevance
“…The possibility of successive accretions of molecular "cloudlets" has also recently been explored (Dullemond et al 2019;Kuffmeier et al 2020). They may also lead to the formation of misaligned second-generation disks that can survive for more than 100 kyr (Kuffmeier et al 2021, see also section 4.3). Other systems show very faint large scale spirals in the outer disk that are reminiscent of low density material being slowly accreted at the outer edge of these objects (e.g., Grady et al 1999;Fukagawa et al 2004;Ardila et al 2007;Huang et al 2020Huang et al , 2021.…”
Section: Streamers Stellar Fly-bys and Tidal Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of successive accretions of molecular "cloudlets" has also recently been explored (Dullemond et al 2019;Kuffmeier et al 2020). They may also lead to the formation of misaligned second-generation disks that can survive for more than 100 kyr (Kuffmeier et al 2021, see also section 4.3). Other systems show very faint large scale spirals in the outer disk that are reminiscent of low density material being slowly accreted at the outer edge of these objects (e.g., Grady et al 1999;Fukagawa et al 2004;Ardila et al 2007;Huang et al 2020Huang et al , 2021.…”
Section: Streamers Stellar Fly-bys and Tidal Interactionsmentioning
confidence: 99%
“…Numerical simulations have suggested that a misaligned companion or planet could warp or even break the disk in two or multiple precessing rings (Nixon et al 2013;Facchini et al 2013;Teyssandier et al 2013;Lodato and Facchini 2013;Nealon et al 2018;Facchini et al 2018;Zhu 2019). Infall events occurring after the initial collapse can also result in misaligned outer disks (Kuffmeier et al 2021). Late type stars are also known to possess a strong magnetic dipole moment, due to their convective nature.…”
Section: Misaligned Inner Disks Radial Flows and Kinematics Of Transi...mentioning
confidence: 99%
“…Together, these observations indicate that many disks are perturbed by their surroundings while planet formation is ongoing. Key theorized consequences of these external perturbations include modification of the total mass budget available for planet formation, disk truncation, inducement of misalignments or instabilities, formation of disk substructures, and stellar outbursts (e.g., Clarke & Pringle 1993;Bae et al 2015;Harsono et al 2011;Manara et al 2018;Cuello et al 2019;Dullemond et al 2019;Kuffmeier et al 2020Kuffmeier et al , 2021Kuznetsova et al 2022). Thus, mapping disk environments is crucial for understanding what processes control protoplanets' formation location and timescale, mass, orbital behavior, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above recognition, Dullemond et al (2019) have proposed that the gas accretion is sporadic in the late stage of star formation and some Class II objects have secondary disks formed by the capture of a cloudlet (see also Küffimeier et al 2019). More recently, Küffmeier et al (2021) have made numerical simulations in which the captured cloud forms an outer disk surrounding a pre-existing inner disk.…”
Section: Introductionmentioning
confidence: 99%